Geoecology Identification Using Landsat 8 for Spatial Planning in North Sulawesi Coastal - Edwin Maulana; Th. Retno Wulan; Dwi Sri Wahyunungsih; Farid Ibrahim; Anggara Setyabawana Putra; Mega Dharma Putra (Faculty of Geography, Universitas Gadjah Mada, 2017)
Abstract Geoecology is a landscape study combined with the social and environmental aspect. The study aims to identify Geoecology of coastal Manado, North Sulawesi. Identification of coastal Geoecology using Landsat 8 supported by SRTM. Data was collected by field survey and taking aerial photo using UAVs. The field survey was conducted to capture the documentation and in-depth interviews. The research method is the interpretation of remote sensing imagery. Data from image interpretation collaborated with field survey data. The results showed that there are three types of coastal that is sandy, rocky and muddy. The sandy comes from karst hills and volcanoes. The rocky and karst hills come from volcanic material that has the character of a big wave. The muddy affected by the presence of the river that carries materials from structural hills. Geoecology based coastal area management is expected to be instrumental in structuring regional integrated and planned.Key words: Geoecology, Landsat, Coastal, North Sulawesi